Evaluasi Peran Dinas Lingkungan Hidup dan Pertanahan Provinsi Sumatera Selatan Dalam Penilaian Dokumen AMDAL - Rian Syafni (xxxx-xxxx, 2020)
Syafni R.  2020.  The role evaluation of environment and land office of south sumatra province in assessing AMDAL documents. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The Environment and Land Office of South Sumatra Province takes important role in AMDAL Document Assessment in South Sumatra Province, but so far there has been no role evaluation related to this assesment. The aim of this research was to evaluate the role of the Environment and Land Office in the AMDAL document assesment. This research was conducted through interviews, direct observation, documentation and literature review. The result was that the AMDAL Assessment Commission which is under the auspices of the South Sumatra Province Environmental and Land office owned a Technical Team consisting of four people certified AMDAL editors and four people certified AMDAL assesors. In addition, the AMDAL Assessment Commission of South Sumatra Province also had experts including Environmental Biologists (1 person), Geophysicist (2 people), Chemical Physicist (1 person), Environmental Economist (1 person), Public Health Expert (1 person) and Regional Planning Expert (1 person). In the AMDAL document assessment,  Environment and Land office  refers to its Standard Operating Procedures (SOP). Every chronology of the AMDAL process starting from the receipt of the KA-ANDAL documents to the issuance of a Technical Recommendation on Environmental Feasibility by the Head of the Environment and Land office of South Sumatra Province was recorded in a log book. The conclusion of this research is that The Environment and Land Office of South Sumatra Province has carried out its role in the AMDAL document properly and in accordance with the appropriate regulations.